Pengaruh Faktor Psikologis Dan Kualitas Informasi Terhadap Keputusan Melakukan Pinjaman Online Melalui Peer-To-Peer Lending Di Masa Pandemi Covid-19 (Studi Kasus Pada Mahasiswa Angkatan 2017 Universitas Pendidikan Ganesha) - Dwiyanti, Erina; Herawati, Nyoman Trisna (Universitas Pendidikan Ganesha, 2021)
The purpose of this research was to determine the partially effect of psychological factors, namely perceived ease, perceived trustworthiness, perceived risk, and quality of information on the decision to make online loans through peer-to-peer lending during the Covid-19 pandemic. This research uses quantitative methods. This research is a correlational study which aims to determine whether there is a relationship between the variables involved in an object or subject under study. The sampling technique was carried out by using proportional purposive sampling. Data obtained through questionnaires distributed via google form to 340 respondents with the criteria of Ganesha University of Education active students who borrow through peer-to-peer lending and earn income regularly every month. The data obtained were then tested and analyzed using the data quality test method, classical assumption test, and multiple linear regression test. The results showed that all independent variables, namely perceived ease, perceived trustworthiness, perceived risk, and quality of information partially had a positive and significant effect on the decision to make online loans through peer-to-peer lending during the Covid-19 pandemic.